Analysis of Lung Capacity Using A Rotary Spirometer Athletes In 18-Year-Old Basketball Athletes At The Bekasi Sniper Basketball Club - Fadhillah Irsyad Rahman; Deden Akbar Izzudin; R. Retna Kinanti Dewi; Habibi Hadi Wijaya; M. Arief Setiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study experienced difficulties during the match and at the end of almost the end of the match the team suffered a defeat due to declining physique which resulted in the match that had previously dominated the match ending in defeat due to the player experiencing fatigue, therefore the researchers wanted to try to analyze the vital capacity of the lungs and v02max owned by athletes using a rotary spirometer and using the bleep test, This type of research uses a Pre experimental method with a quantitative descriptive approach and in the form of a one-shot case study. data collection in this research using a rotary spirometer and a bleep test data test The results of the research were carried out on Wednesday and Sunday, May 2 and 7, 2024 with an age group of 18 years carried out with a sample of 12 athletes, The percentage of lung capacity levels and vo2max that the lung capacity level and vo2max of the 18-year-old Bekasi sniper basketball athletes with a total number of 100% or the total number of this sample is 12 athletes who conducted the test.